1968
DOI: 10.1039/tf9686400308
|View full text |Cite
|
Sign up to set email alerts
|

Electronic spectra of the free allyl radical and some of its simple derivatives

Abstract: Electronic spectra in the 2100-2500 8, region, were reported for the allyl radical, the P-methallyl radical, the cc-methallyl radical, the p-ethallyl radical and the cyclopentenyl radical. The vibrational structures of the allyl and P substituted radicals indicate that in the main regions of absorption, the a(C-13) stretching frequency is excited. A single band progression observed in flashed allyl cyanide, was tentatively assigned to a free radical derived from pyrrole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
48
1

Year Published

1975
1975
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 0 publications
8
48
1
Order By: Relevance
“…The 2-methylallyl radical has been studied using a range of spectroscopic methods including electron spin resonance [1], photoelectron [2], absorption [3,4], resonance Raman [5,6], and photofragment action spectroscopy [7]. The 2-methylallyl radical was first produced in the gas phase by Callear and Lee [3] by pyrolysis of various radical precursors. The authors reported a structured absorption in the ultraviolet (UV) in the range between 220 and 260 nm.…”
Section: Introductionmentioning
confidence: 99%
“…The 2-methylallyl radical has been studied using a range of spectroscopic methods including electron spin resonance [1], photoelectron [2], absorption [3,4], resonance Raman [5,6], and photofragment action spectroscopy [7]. The 2-methylallyl radical was first produced in the gas phase by Callear and Lee [3] by pyrolysis of various radical precursors. The authors reported a structured absorption in the ultraviolet (UV) in the range between 220 and 260 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Its photochemistry upon UV excitation is thus of considerable relevance for tropospheric chemistry and combustion. The UV band system, starting at 250 nm and observed first in absorption, 1 was studied by resonant multiphoton ionization ͑MPI͒, 2-5 allowing the identification of a large number of vibronic bands and their assignment to the electronic B, C, and D states, which are strongly coupled with each other. Resonance Raman spectra from these states were also recorded, 6 but no fluorescence has been observed, despite the large oscillator strength calculated for the C←X transition, 7 indicating short lifetimes.…”
Section: ͓S0021-9606͑97͒05143-x͔mentioning
confidence: 99%
“…5 The location of the electronic A state was derived from an unassigned, but well resolved absorption spectrum. 6 The UV band system starting at 250 nm was studied in detail by absorption spectroscopy, 7 multiphoton ionization, [8][9][10][11][12] and resonance Raman spectroscopy. 4,13,14 Excited state geometries were derived from partially rotationally resolved MPI spectra.…”
Section: Introductionmentioning
confidence: 99%